Self-reported health behaviors, including sleep, correlate with doctor-informed medical conditions: data from the 2011 Health Related Behaviors Survey of U.S. Active Duty Military Personnel. - Hruby, Adela.; Lieberman, Harris R.; Smith, Tracey J. (2018)
Background: Health behaviors and cardiometabolic disease risk factors may differ between military and civilian populations; therefore, in U.S. active duty military personnel, we assessed relationships between demographic characteristics, self-reported health behaviors, and doctor-informed medical conditions.; Keywords: Army, Navy, Air force, Marine corps, Coast guard, Cardiometabolic risk, Exercise, Sleep, Survey.; Springer Open.